Interactive effects of life cycle and monocot-dicot lineage on genome size–trait relationships in angiosperms: a phylogenetically informed analysis - Liu, Guolan; Wen, Yin; Fu, Peili; Cao, Qiqi; Cui, Qian; Du, Wen; Chen, Hao; Zhao, Wanli (Frontiers in Plant Science, 2025)
IntroductionGenome size in angiosperms exhibits extraordinary variation, influencing a wide array of biological and ecological characteristics. Although prior studies have established links between genome size and certain functional traits, how the interaction between two fundamental axes of angiosperm diversity—life cycle (annual vs. perennial) and monocot-dicot distinction—shapes group-specific variation in genome size and its relationship with plant functional traits remains insufficiently understood.MethodsWe assembled a comprehensive dataset encompassing 2,285 angiosperm species from 186 families, measuring genome size (1C-value) and monoploid genome size (1Cx-value) to account for polyploidy, as well as key size-related traits, including plant height and the length and width of leaves, flowers, fruits, and seeds. To evaluate the relationships between genome size and these functional traits while controlling for shared evolutionary history, we conducted phylogenetic generalized least squares (PGLS) analyses.ResultsThe results indicated that the interaction between life cycle and monocot-dicot distinction is a primary determinant of both 1C and 1Cx variation, with perennial monocots exhibiting the largest 1C and 1Cx values and a significant interactive effect between these two axes of diversity. Patterns of correlation between genome size metrics (1C, 1Cx) and functional traits are group-specific and sometimes reversed, reflecting divergent adaptive strategies—for example, genome size (1C) is positively correlated with plant height in annuals but negatively in perennials. Phylogenetic correction revealed that some associations, such as the negative correlation between genome size and plant height in perennials, are largely driven by shared ancestry and disappear after accounting for phylogeny, whereas others, such as the positive correlation between genome size (1C, 1Cx) and petal length, remain robust across groups, indicating a conserved adaptive relationship. The use of 1Cx confirmed that observed patterns reflect fundamental genome architecture rather than solely polyploidy effects.DiscussionThese findings demonstrate that the interplay between life cycle and monocot-dicot distinction fundamentally shapes genome size (1C, 1Cx)–trait relationships in angiosperms, providing new insights into the evolutionary and adaptive mechanisms underlying plant diversity.